Prevalence and Risk Factors of Smoking, and Tobacco use among Secondary School Boy Students in Tabuk Region, Saudi Arabia - Tawfik M. Ghabrah (Journal of King Abdulaziz University: Medical Sciences, 2023)
As tobacco epidemic continues to increase among adolescents, tobacco control programs based on actual field studies are crucially needed. A cross-sectional study was conducted in Tabuk region to determine the prevalence and risk factors of tobacco use among secondary school boy students. A three-stage stratified random sampling design was used to recruit a sample of 1,680 students from 15 secondary schools. A self-administrated Arabic questionnaire was used to collect the required data. A descriptive and analytic statistical analysis was done. Overall prevalence of cigarette and shisha smoking was 25.7% and 25.9%, respectively. Prevalence of current daily and non-daily smokers was 16.3% and 9.4%, respectively. Prevalence of shisha smokers was 4.3% and 21.6% on regular and non-regular basis, respectively. Odds ratios of important risk factors were: Nationality (1.42), fathers’ smoking (1.42), mothers’ smoking (2.74), school absenteeism (2.96), sleep disturbance (2.26), and mothers’ living status (1.80). Important reasons for smoking were entertainment (43.2%), overcoming the feeling of oppression (36.1%) and peer pressure (11.0%). The majority of students (70.5%) addressed the desire for quitting smoking for health promotion (48.9%); Islamic rules (25.5%) and family dislike (19.9%) reasons. In conclusion, a quarter of the high school students were smokers which necessitate an urgent intervention.